1992
DOI: 10.1063/1.463942
|View full text |Cite
|
Sign up to set email alerts
|

The average number of kinks of a short polyelectrolyte chain: A Monte Carlo study

Abstract: An interesting connection between the mean straight length 〈ls〉 and the defined average number of kinks 〈nkink〉 in a polyelectrolyte chain configuration is found and described. 〈nkink〉 is found to be the dominant parameter throughout the entire range of the Bjerrum length λ and very sensitive to salt concentration. Identification of λm where (nkink values for various chain lengths coincide, as a percolation threshold is suggested. Considering the kink as a bond, it is found to be much more significant than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

1992
1992
2003
2003

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 11 publications
0
13
1
Order By: Relevance
“…Unlike the longer chain polymer, turbidity occurred even at a lower part of binding (β < 0.5) for the Asp12 sample, while in other systems a precipitate usually appears when the binding becomes saturated just below β = 1. This phenomenon may be due to the conformational change of polymer chain from the extended random coil to globules, which may happen more easily in oligoelectrolyte like Asp12, since the short chain is less stretched than the infinite one . The conformational change would make the aggregates of the hydrophobic polymer−surfactant complex with more ease and subsequent precipitation in the early stage of binding.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the longer chain polymer, turbidity occurred even at a lower part of binding (β < 0.5) for the Asp12 sample, while in other systems a precipitate usually appears when the binding becomes saturated just below β = 1. This phenomenon may be due to the conformational change of polymer chain from the extended random coil to globules, which may happen more easily in oligoelectrolyte like Asp12, since the short chain is less stretched than the infinite one . The conformational change would make the aggregates of the hydrophobic polymer−surfactant complex with more ease and subsequent precipitation in the early stage of binding.…”
Section: Resultsmentioning
confidence: 99%
“…Note the almost identical values of h for small n over the entire investigated range of λ (i.e., h D (2) (5) ). These values are lower than the values of h D(16) , h D(29) , and h D(30) .…”
Section: Parameter Definitions Results and Discussionmentioning
confidence: 88%
“…Figure 3 describes values of D(2), D(3), D(4), and D(5) for various λ and N ) 16 at various salt concentrations. For C ) 0, it is apparent that the slope of the curve for D (5) is steeper than that for D (4) and that of D(4) is steeper than that of D(3) etc. It is interesting to note that in Figure 3, 5, and 6 of ref 6, we found that, when we divided D(n) by n 2 (n 2 is the squared end-to-end distance at the rodlike maximum stretch), chains of small n are relatively more stretched (less flexible) than chains of large n, i.e., the values of the "normalized" D(n) are higher for n ) 2 than for n ) 3 and those of n ) 3 are higher than for n ) 4 etc.…”
Section: Parameter Definitions Results and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Treatments of electrostatic persistence lengths and excluded volume and their relation to polyelectrolyte conformations and interactions were first made by Odijk [1,2] , Skolnick and Fixman [3,4] . Because precise analytical solutions to the excluded volume problem do not exist, there have also been computer simulation approaches [5][6][7][8][9] . A general review of polyelectrolytes was given recently by Fo¨rster and Schmidt [10] .…”
mentioning
confidence: 99%